1984
DOI: 10.1039/c39840000191
|View full text |Cite
|
Sign up to set email alerts
|

Metal carbonyl derivatives of divalent lanthanoids. Bis(tetracarbonylcobalt)-samarium, -europium, and -ytterbium

Abstract: The first metal carbonyl derivatives, L~[CO(CO)~]~.(THF), (THF = tetrahydrofuran; n = 3, 4), of divalent lanthanoids Ln (Ln = Sm, Eu, Yb) were prepared by treating Hwith an excess of Sm, Eu, or Yb in THF at room temperature; the title complexes were also formed in high yields from the reaction of stoicheiometric amounts of the appropriate Ln12 compounds and TICO(CO)~.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This initial report was followed by many others from different laboratories. The most common reactions involving transition-metal carbonyl complexes and rare-earth reagents include a) salt elimination from alkali metal or thallium carbonylmetallates and (partly substituted and/or solvated) rare-earth halides, [68] b) transmetalation as in the example stated above, [67,69] c) oxidative www.chemeurj.org addition of rare earths or their amalgams to transition-metal carbonyl halides, [70] and d) reduction of (partly substituted) transition-metal carbonyls with rare-earths or their amalgams. [68c, 71] The choice of transition-metal fragments which contained carbonyl ligands in all early studies was guided by the assumption that the numerous stable metal carbonylates-effectively stabilized by the carbonyl ligands ability to delocalize negative charges-could be suitable Lewis bases to form metal-metal bonds with the Lewis-acidic rare-earth center.…”
Section: Rare-earth-transition Metal Bonds (Re-tm)mentioning
confidence: 99%
See 1 more Smart Citation
“…This initial report was followed by many others from different laboratories. The most common reactions involving transition-metal carbonyl complexes and rare-earth reagents include a) salt elimination from alkali metal or thallium carbonylmetallates and (partly substituted and/or solvated) rare-earth halides, [68] b) transmetalation as in the example stated above, [67,69] c) oxidative www.chemeurj.org addition of rare earths or their amalgams to transition-metal carbonyl halides, [70] and d) reduction of (partly substituted) transition-metal carbonyls with rare-earths or their amalgams. [68c, 71] The choice of transition-metal fragments which contained carbonyl ligands in all early studies was guided by the assumption that the numerous stable metal carbonylates-effectively stabilized by the carbonyl ligands ability to delocalize negative charges-could be suitable Lewis bases to form metal-metal bonds with the Lewis-acidic rare-earth center.…”
Section: Rare-earth-transition Metal Bonds (Re-tm)mentioning
confidence: 99%
“…This initial report was followed by many others from different laboratories. The most common reactions involving transition‐metal carbonyl complexes and rare‐earth reagents include a) salt elimination from alkali metal or thallium carbonylmetallates and (partly substituted and/or solvated) rare‐earth halides,68 b) transmetalation as in the example stated above,67, 69 c) oxidative addition of rare earths or their amalgams to transition‐metal carbonyl halides,70 and d) reduction of (partly substituted) transition‐metal carbonyls with rare‐earths or their amalgams 68c. 71…”
Section: Known Compoundsmentioning
confidence: 99%
“…Several synthetic approaches towards isocarbonyl‐bridged RE–TM complexes were established over the past four decades. Adduct formation,15 reduction of transition‐metal carbonyls with divalent rare‐earth complexes17 or rare‐earth amalgams,18 salt elimination,19 and transmetalation20 are the most common routes to these complexes. The resulting complexes offer the potential to be used as catalysts in Fischer–Tropsch reactions21 or as starting materials for perovskite‐type oxides, which are used as methane oxidation catalysts 22.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, synthetic procedures toward Ln(II, III)−M carbonyl compounds were developed, and the structural relationship of the metal combinations was probed. Preparative methods 2b,4 for these heterometallics generally utilize simple adduct formation, metathesis, 5c,, M−X bond cleavage, M−M bond cleavage (1e - transfer, ,6c, reduction in liquid ammonia, amalgam reduction 11 ), and transmetalation. 2c,6b,, Cumulatively, these studies have revealed three possible kinds of Ln−M interactions (Chart ): Ln−M direct bonds ( I ), solvent-separated ion pairs ( II ), and isocarbonyl linkages ( IIIa − IIIc ).
1
…”
Section: Introductionmentioning
confidence: 99%
“…While it is difficult to separate kinetic and thermodynamic contributions to complex formation, the nature of the Ln−M bonding is highly contingent upon the nucleophilicity of the transition metal in the carbonylate anion, [M(CO) y ] n - . Specifically, the relative Lewis basicities of M, the CO ligands, and the solvent determine the type of interaction between Ln and M. Direct Ln−M bonded systems ( I , Chart ) are yielded when the transition-metal center is the most nucleophilic constituent (i.e., electron density resides on M). ,10a,b A solvent-separated ion pair ( II ) results when the electron-donating ability of the solvent exceeds that of [M(CO) y ] n - . ,6c,11c, If the carbonyl oxygens are more Lewis basic than M, then an isocarbonyl bridge ( IIIa − c ) to Ln is formed. 2c,6d, Low polarity or nonnucleophilic solvents can also favor the formation of an isocarbonyl even when [M(CO) y ] n - is a weak nucleophile. 9a, While the two types of isocarbonyl interactions η 2 , μ 2 -CO ( μ -CO; IIIa ) 2c,6d,9a,c,e,13 and η 2 , μ 3 -CO 9b,d ( IIIb ) are known, Ln−M examples of η 2 , μ 4 -CO bridges ( IIIc ) have not been reported …”
Section: Introductionmentioning
confidence: 99%